(untitled) (Journal of Parents and Teachers, 2023)
This article analyzes key elements of the Spiritual Exercises of St. Ignatius of Loyola and the role of the companion according to the Annotations to the Exercises, and then presents how, in the light of these, the profile of the Ignatian educator is defined, as well as some "practical lessons" for the educator-pupil relationship.